Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1093/nar/gkp870
|View full text |Cite
|
Sign up to set email alerts
|

Sequence context outside the target region influences the effectiveness of miR-223 target sites in the RhoB 3′UTR

Abstract: MicroRNAs (miRNAs) are 21–22 nucleotide regulatory small RNAs that repress message translation via base-pairing with complementary sequences in the 3′ untranslated region (3′UTR) of targeted transcripts. To date, it is still difficult to find a true miRNA target due to lack of a clear understanding of how miRNAs functionally interact with their targeted transcripts for efficient repression. Previous studies have shown that nucleotides 2 to 7 at the 5′-end of a mature miRNA, the ‘seed sequence’, can nucleate mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 66 publications
4
56
0
Order By: Relevance
“…29 Although eNOS levels were decreased in pre-miR-223-overexpressing cells, there was no identifiable miR-223 seeding sequence in the eNOS 3′UTR, and it seems that miR-223, like miR-221 and miR-222, 29 has only an indirect effect on eNOS expression. The 3′UTR of RhoB was reported previously to be targeted by miR-223 in different cell lines, 21 and the protein has been implicated in angiogenesis. [22][23][24] Therefore, we concentrated on determining a link between miR-223 and β1 integrin expression.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…29 Although eNOS levels were decreased in pre-miR-223-overexpressing cells, there was no identifiable miR-223 seeding sequence in the eNOS 3′UTR, and it seems that miR-223, like miR-221 and miR-222, 29 has only an indirect effect on eNOS expression. The 3′UTR of RhoB was reported previously to be targeted by miR-223 in different cell lines, 21 and the protein has been implicated in angiogenesis. [22][23][24] Therefore, we concentrated on determining a link between miR-223 and β1 integrin expression.…”
Section: Discussionmentioning
confidence: 98%
“…However, no obvious seeding sequence for miR-223 could be detected within the eNOS 3′UTR, indicating that eNOS is likely to be an indirect rather than a direct target. Given that RhoB has already been identified as a miR-223 target 21 and has been implicated in angiogenesis, [22][23][24] we concentrated on β1 integrin.…”
Section: Identification Of Mir-223 Target Proteins In Endothelial Cellsmentioning
confidence: 99%
“…Though miR-132 and miR-212 share the same seed sequence, the rest of their nucleotide sequences differ from one another. These non-seed regions play an important role in directing mRNA targeting, and therefore potentially have a dramatic effect on the regulatory capacity of each miRNA (Breving and Esquela-Kerscher 2010;Sun et al 2010). Furthermore, while their transcriptional expression may be quite similar, miR-132 and miR-212 may undergo substantially different posttranscriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that miRNA-mediated regulation might require the presence of an ARE sequence [42][43][44]. As the miR-101 and miR-600 binding sites overlap with the ARE-6074 motif and the miR-384 binding site overlaps with the ARE-5698 motif ( fig.…”
Section: Transcription Factors Involved In the Regulation Of Cftr Temmentioning
confidence: 95%